'The most trustworthy writers on our Blacks': Edward M. Curr's Critique of Armchair Anthropology. Issue 3 (8th November 2016) - Furphy, Samuel
Abstract : Edward M. Curr was a controversial figure in Australian anthropology during its formative period. In his major work, The Australian Race (1886), he used the techniques of comparative philology to develop a theory of Aboriginal racial origins. The most enduring legacy of Curr's publication is its linguistic data, but at the time of its publication it was just as notable for its predominantly negative assessments of fellow ethnologists. While prominent contemporaries such as A.W. Howitt and Lorimer Fison drew authority from their connections to international scholarly networks, Curr eschewed the theoretical debate that surrounded his endeavour and emphasised that he (and his network of correspondents) had personal knowledge of Aboriginal people 'in their savage state.' His work might be viewed as a significant early critique of armchair anthropology and a counterpoint to the then ascendant social evolutionary paradigm; yet, equally, the limitations of his own methodology and the politicised nature of his scholarly intervention are evident. This article argues that Curr was not simply prioritising field research, as he himself knew the value of correspondents; rather, he was privileging the views of the old colonists over more recently arrived supposed experts.